2003
DOI: 10.1163/156856203322381410
|View full text |Cite
|
Sign up to set email alerts
|

Cell attachment and biocompatibility of polytetrafluoroethylene (PTFE) treated with glow-discharge plasma of mixed ammonia and oxygen

Abstract: The plasma generated from a gas mixture of NH3 plus O2 (NH3 + O2) has been used to impart unique chemical and biological characteristics to polytetrafluoroethylene (PTFE). PTFE treated with NH3 + O2 plasma was physiochemically distinct from surfaces treated with plasma of either NH3 or O2 alone, as determined by electron spectroscopy for chemical analysis (ESCA). The contact angle analysis revealed that the PTFE surfaces became less hydrophobic after plasma treatments. ESCA results indicate the presence of oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 31 publications
4
72
1
Order By: Relevance
“…C-C bond was not detected on the surface at all. A rather low concentration of nitrogen found on the PTFE surface (as compared with the results obtained by other authors [7,12,17] ) is probably due to extremely weak interaction of nitrogen positive ions in our plasma. For instance, at our experimental conditions we used inductively coupled plasma at a rather high pressure which is characterized by low kinetic energy of ions at the surface, while other authors used capacitively coupled plasma at lower pressure.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…C-C bond was not detected on the surface at all. A rather low concentration of nitrogen found on the PTFE surface (as compared with the results obtained by other authors [7,12,17] ) is probably due to extremely weak interaction of nitrogen positive ions in our plasma. For instance, at our experimental conditions we used inductively coupled plasma at a rather high pressure which is characterized by low kinetic energy of ions at the surface, while other authors used capacitively coupled plasma at lower pressure.…”
Section: Discussionsupporting
confidence: 69%
“…Free radicals that are created on a polymer surface during treatment in nitrogen plasma can react with oxygen and furthermore, free radicals that remain on the surface after the treatment will react with oxygen when the surface is exposed to the atmosphere. [1,12] When treating PTFE foil in nitrogen plasma for 10 min the N-concentration at the surface is little lower -about 2.5 at.%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies using plasma-treated polymer surfaces with Ar, O 2 , NH 3 , or N 2 reported increasing the surface wettability and improving the cell adhesion or spreading 9,10 . In most studies, however, the ranges of surface wettability employed were narrow; 46-67degrees 7 ,…”
Section: Discussionmentioning
confidence: 99%
“…Similar to metals and metal alloys, cell attachment on polymers can also be modulated by plasma treatment. The application of glow-discharge plasma of mixed ammonia and oxygen on polytetrafluoroethylene surfaces reduced the hydrophobicity and increased the attachment of aorta endothelial cells (Chen et al, 2003). Furthermore, an oxygen plasma has been shown to improve surface attachment of mouse fibroblasts L-929 on thermoplastic polyetherurethane used for gastric implants (Schlicht et al, 2010).…”
Section: Creation Of Bioactive Surfacesmentioning
confidence: 99%